1991
DOI: 10.1002/gps.930060707
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and diagnosis of alcoholism in the elderly (a review)

Abstract: The authors review the research on alcoholism in the elderly. There is evidence that prevalence studies underestimate its extent. Geriatric alcoholism often eludes detection as diagnostic criteria generally used for the adult may not apply to the elderly population. Issues pertaining to clinical features, classification and pattern of use are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Research in the 1960s and 1970s identified that abuse of alcohol does occur in this group (Rosin and Glatt, 1971), though it is less common than in younger adults (Warheit and Auth, 1984). Research in the United States and Britain has shown prevalence rates of 413% in community surveys (Meyers et al, 1982;Calahan et al, 1969;Barnes, 1979;Bridgewater et al, 1987), the rate in institutions being much higher, perhaps up to 60% (Caracci and Millar, 1991). Alcohol has been implicated in up to 50% of medical and psychiatric hospital admissions (McCusker et al, 1971;Simon et al, 1968;Gaitz and Bayer, 1971).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research in the 1960s and 1970s identified that abuse of alcohol does occur in this group (Rosin and Glatt, 1971), though it is less common than in younger adults (Warheit and Auth, 1984). Research in the United States and Britain has shown prevalence rates of 413% in community surveys (Meyers et al, 1982;Calahan et al, 1969;Barnes, 1979;Bridgewater et al, 1987), the rate in institutions being much higher, perhaps up to 60% (Caracci and Millar, 1991). Alcohol has been implicated in up to 50% of medical and psychiatric hospital admissions (McCusker et al, 1971;Simon et al, 1968;Gaitz and Bayer, 1971).…”
mentioning
confidence: 99%
“…A number of studies have highlighted the need to identify specific symptoms and signs that indicate abuse of alcohol in the elderly (Brody, 1982;Caracci and Millar, 1991;Graham, 1986;Wattis, 198 1). Suggestions include falls, incontinence, selfneglect, accidents, burns, blackouts, debility, confusion.…”
mentioning
confidence: 99%
“…Only three subjects were CAGE positive and thus DISCUSSION Our principal finding is of a striking absence of current alcohol abuse in this elderly population, in contrast to studies of elderly populations in North America (Caracci and Miller, 1991). We believe it is important to report this negative finding.…”
Section: Cage Resultsmentioning
confidence: 63%
“…Finally, the low socioeconomic status of the population may limit availability of alcohol and thus, secondarily, prevent abuse. We favour the last explanation, as careful examination of North American studies reveals that the populations are frequently of high social economic status (Caracci and Miller, 1991).…”
Section: Cage Resultsmentioning
confidence: 96%
See 1 more Smart Citation